TRAINER KIT MODEL PEMBELAJARAN ANEKA SENSOR BERBASISKAN MIKROKONTROLER UNTUK SISWA SMA - Calvinus, Yohannes; Setyaningsih, Endah; Fat, Joni; Utama, Hadian Satria (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Santa Laurensia High School is the largest school in Alam Sutera, which uses holistic learning in teaching students. The holistic learning model emphasizes teaching through a lot of supporting information. Santa Laurensia High School is also considered as one of the best schools in science. The electronics learning program at this school is deemed insufficient, therefore the school held a Science day to share knowledge about electrical engineering assisted by Lecturers and students of Tarumanagara University's Electrical Engineering Undergraduate Study Program for students. This training uses science and technology simulations with trainer kit modules and introduces internet of things technology. In addition to the Internet of things technology, the purpose of this training is to provide an introduction to students about some sensors and how they can be controlled. This training uses a trainer kit module to help students understand the material quickly and correctly. This training was attended by a community at school (science club) as many as 15 students from Santa Laurensia High School. In addition to introducing sensors and internet technology, students also bring modules that have been programmed to demonstrate the sophistication of an Internet of things technology using branding from a product called Mecal. The method of measuring success used is through the pre-test and post-test questionnaire method, which has proven to have helped students understand Electrical Engineering components. With the many benefits obtained from the training held at Santa Laurensia High School, it can be concluded that this program has succeeded in increasing students' knowledge of electrical engineering. SMA Santa Laurensia merupakan sekolah terbesar di Alam Sutera, yang menggunakan pembelajaran holistik dalam mengajar siswa. Model pembelajaran holistik yang menekankan pengajaran melalui banyak informasi pendukung. SMA Santa Laurensia juga dianggap sebagai salah satu sekolah terbaik dalam hal sains. Program pembelajaran elektronika di sekolah ini dirasa belum cukup, oleh karena itu sekolah mengadakan Science day untuk berbagi pengetahuan tentang teknik elektro yang dibantu oleh Dosen dan mahasiswa Program Studi Sarjana Teknik Elektro Universitas Tarumanagara untuk para siswa. Pelatihan ini menggunakan simulasi iptek dengan modul trainer kit dan memperkenalkan teknologi internet of things . Selain teknologi Internet of things , tujuan dari pelatihan ini adalah untuk memberikan pengenalan kepada siswa tentang beberapa sensor dan bagaimana sensor tersebut dapat dikontrol. Pelatihan ini menggunakan modul trainer kit untuk membantu para siswa dalam memahami materi dengan cepat dan benar. Pelatihan ini diikuti oleh suatu komunitas di sekolah (club sains) sebanyak 15 siswa/i SMA Santa Laurensia. Selain memperkenalkan sensor dan teknologi internet, mahasiswa juga membawa modul yang telah di program untuk mendemonstrasikan kecanggihan dari suati teknologi Internet of things menggunakan branding dari Produk bernama Mecal. Metode pengukuran keberhasilan yang digunakan adalah melalui metode kuisioner pre-test dan post-test, yang terbukti telah membantu para siswa dalam memahami komponen Teknik Elektro. Dengan banyaknya manfaat yang didapatkan dari pelatihan yang diselenggarakan di SMA Santa Laurensia, dapat disimpulkan bahwa program ini telah berhasil meningkatkan pengetahuan para siswa tentang teknik elektro.